P050 Analysis of posaconazole therapeutic drug monitoring in paediatric haematology and oncology patients. Issue 7 (19th June 2019) - Donald, Natalie; Edwards, Ruth; Thomson, Alison
Abstract : Posaconazole is a broad spectrum triazole antifungal with activity against a range of invasive fungal pathogens including Candida and Aspergillus species. 1 Due to its range of activity it has been shown, by randomised controlled trials, to be superior to fluconazole and itraconazole for prevention of fungal infection in neutropenic patients, 2 as well as being cost saving. 1 Fungal prophylaxis with posaconazole has become the drug of choice within a paediatric cancer unit due to its broad spectrum of activity however there are significant differences in bioavailability of the suspension and tablet preparations and there is limited data relating to its use in the paediatric population. Objective: To determine if the paediatric cancer unit is undertaking effective dosing and appropriate therapeutic drug monitoring (TDM) of posaconazole in paediatric haematology and oncology patients. Methods: A retrospective analysis of clinical data from 38 paediatric patients treated with posaconazole was undertaken. Patients received either 18–24-mg/kg/day posaconazole suspension in divided doses (maximum 800-mg/day, 3 or 6–8-mg/kg/day posaconazole tablets (maximum 300-mg/day). Compliance with this guidance, initial and subsequent levels, efficacy and tolerability were analysed. Setting: The study was undertaken within the XXXX cancer unit; data for patients treated with posaconazole between January 2016 and August 2017 was reviewed. Key findings: There was good compliance with the dosing advice for liquid and tablet posaconazole with 82% of patients dosed correctly. Due to this, the initial trough level of ≥0.7 mg/L was achieved in 82% of patients within 14 days of treatment initiation; there were no significant differences between formulations. Trough levels were monitored on a monthly basis for 71% of patients but dose adjustments were necessary in 34% of patients. Posaconazole had a good tolerability profile during the study with most side effects resolving on continuation of treatment however one patient had to discontinue the drug due to widespread rash. No patients developed a fungal infection whilst on posaconazole. Conclusion: Safe and effective dosing and monitoring of posaconazole suspension and tablet formulations has been undertaken at the XXXX. Trough levels attained the desired target concentration of ≥0.7 mg/L in the majority of patients but dose adjustments were required with both formulations emphasising the need for regular TDM. Posaconazole was well tolerated and clinically effective in preventing fungal infection indicating its appropriateness in this patient group. From this review, a guideline for initiation and appropriate TDM of posaconazole can be developed. References: Dranitsaris G, Khoury H. Posaconazole versus fluconazole or itraconazole for prevention of invasive fungal infections in patients undergoing intensive cytotoxic therapy for acute myeloid leukemia or myelodysplasia: a cost effectiveness analysis. Supportive Care in Cancer . 2011; 19(11): 1807–1813. Cornely O, Maertens J, Winston D, et al. Posaconazole vs. Fluconazole or Itraconazole in Patients with Neutropenia. New England Journal of Medicine . 2007; 356(4): 348–359. Bernardo V, Cross S, Crews K, et al. Posaconazole Therapeutic Drug Monitoring in Paediatric Patients and Young Adults with Cancer. The Annals of Pharmacotherapy . 2013; 47: 976–983.